Asymptotic behavior of the Gerber–Shiu discounted penalty function in the Erlang(2) risk process with subexponential claims - Kočetova, Jelena; Šiaulys, Jonas (Nonlinear Analysis: Modelling and Control, 2011)
We investigate the asymptotic behavior of the Gerber–Shiu discounted penalty function ɸ(u) = E(e−δT 1{T
Keywords: Gerber–Shiu discounted penalty function; subexponential claim size, defective renewal equation